Micropatterning of lanthanide complex species onto self-cracking flexible transparent films and their photophysical properties. (April 2017) - Wen, Qin; Yang, Jinglian; Li, SongRu; Gao, Jinwei; Lu, Xubing; Wang, Qianming
Graphical abstract: We reported micromolding technique for the patterning of lanthanide luminescent layers onto robust sheets. Europium antibiotic complex, BaMoO4 :Eu 3+ and CePO4:Tb 3+ have been incorporated into the substrate with the aid of self-cracking of egg white film. Highlights: Micropatterning of lanthanide edifices on flexible sheets has been reported. Visible red/green emissions were observed. The luminescent silicone stamps exhibited pH dependence. Abstract: Based on lanthanide optical materials, flexible and transparent luminescent films have been fabricated based on self-cracking micro-pattern on polydimethylsiloxane (PDMS) substrates. The morphology and photoluminescence were studied based on the self-assembly structures. The corresponding intra-molecular energy transfer and photophysical properties were evaluated. Results demonstrated that both lanthanide complex and phosphors could be well controlled and stamped onto the designed cracking micropatterns with red or green emissions. The effects of pH value changes on the luminescent features of the films, as well as its influence on europium complex have been extensively studied. Investigation on transmittance and mechanical properties indicated that the optical and structural quality of such functional films will be potentially useful in the novel design of light-emitting devices or for sensing applications.